Regulation of Baboon Fetal Pituitary Prolactin Expression by Estrogen - Pepe, Gerald J. (Society for the Study of Reproduction, Inc., 2009)
We previously showed that fetal adrenal fetal zone growth was increased and the number of follicles in the fetal ovary reduced in baboons in which estradiol was suppressed by treatment with the aromatase inhibitor letrozole between mid and late gestation periods. Because adrenal/ovarian development was restored in animals treated with letrozole and estradiol, and both tissues express estrogen receptor, we proposed that estrogen regulates fetal adrenal/ovary development via a direct action. However, because prolactin can modulate fetal adrenal and adult pituitary/ovarian function, the current study determined whether estrogen action involved estradiol-regulated changes in fetal prolactin/luteinizing hormone (LH) expression. Fetal prolactin levels and the number of prolactin-positive fetal pituitary cells (per 0.37 mm(2)) were increased (P < 0.01) between mid (6 ± 1 ng/ml; 15.8 ± 2.4) and late (257 ± 28 ng/ml; 57.3 ± 5.1) gestation, reduced (P < 0.01) in late-gestation fetuses in which estradiol was suppressed (>95%) by letrozole (61 ± 11 ng/ml; 19.3 ± 2.0), and minimally but not significantly increased by letrozole and estradiol (99 ± 11 ng/ml; 32.7 ± 5.2). In contrast, the number of LH-positive fetal pituitary cells decreased (P < 0.01) between mid (48.8 ± 9.5) and late (17.4 ± 3.2) gestation, remained elevated (P < 0.01) in estrogen-suppressed animals (56.6 ± 5.1), and was partially but not significantly decreased by letrozole-estradiol (28.8 ± 5.2). We conclude that estrogen regulates fetal pituitary prolactin and LH expression and fetal prolactin levels. However, because prolactin and LH expressions in estrogen-suppressed fetuses were inversely related to previously demonstrated changes in adrenal/ovarian development, we propose that estrogen regulates the fetal ovary and adrenal gland directly and not via action on the fetal pituitary gland.